Extra-community international minor abduction: issues regarding the obligation of the prompt return of children from the 1980 Hague Convention in Spanish practice - Cordero Álvarez, Clara Isabel (CUADERNOS DE DERECHO TRANSNACIONAL, 2021)
In cases of child abduction that the Spanish courts must resolve as the country of destination of the minor, the correct interpretation of the international obligations assumed by our State in this area is required. The fundamental instrument in a case of international child abduction from a non-EU country is the 1980 Hague Convention. This convention obliges all contracting States to order the return of the child forthwith -who has been illegally transferred or detained in their territory- if no more than one year has elapsed since the wrongful removal or retention took place. This general rule -the main one- has a significant exception that allows order the return of the child even after that period unless the minor is now settled in its new environment. In practice, the computation of the term regulated by the general rule raises different non-standardized interpretive issues for the Contracting States, what conditions the result of the restitution process. The application of the national - procedural – measures regulated to comply with the Convention´s provisions, should not affect, by itself, that term to base decisions on the refusal of restitution, as seems to be the national case law approach using principle of the best interests of child. Other considerations may carry the risk of contravening the purposes of the international instrument.